Dinamika Kewenangan Mahkamah Konstitusi Dalam Menyelesaikan Perselisihan Hasil Pemilihan Umum Kepala Daerah Serta Implikasinya Terhadap Pemilihan Umum Serentak Tahun 2024 - Dikri Purnama, Muhamad; Rosidin, Utang (Adagium: Jurnal Ilmiah Hukum, 2025)
This study aims to analyze the development of the Constitutional Court’s authority in resolving disputes over the results of regional head elections (PHP Kada) and to assess its implications for the coherence of the electoral legal system ahead of the 2024 Simultaneous Elections. Initially, the authority to adjudicate PHP Kada was vested in the Supreme Court based on Article 106 paragraph (1) of Law Number 32 of 2004 on Regional Government. Due to inefficiencies and increased judicial burden, the authority was transferred to the Constitutional Court through Law Number 12 of 2008. However, Constitutional Court Decision Number 97/PUU-XI/2013 declared that regional elections are not part of the national election regime under Article 22E of the 1945 Constitution, and the Court’s jurisdiction was therefore temporary pending the establishment of a specialized judicial body. The legislature's failure to implement this mandate has prolonged legal uncertainty. Subsequently, Decision Number 85/PUU-XX/2022 affirmed that the Court’s authority is permanent as a form of constitutional protection for citizens' voting rights. This study applies a normative juridical method using statutory and conceptual approaches. The findings recommend explicitly incorporating the Constitutional Court's authority into the 1945 Constitution to reinforce institutional legitimacy, ensure legal certainty, and safeguard the sustainability of the simultaneous election system within a constitutional framework.